Chalcogen‐Bonding Catalysis: From Neutral to Cationic Benzodiselenazole Scaffolds. Issue 7 (27th June 2018) - Benz, Sebastian; Besnard, Celine; Matile, Stefan
Abstract : Benzodiselenazoles (BDS) are emerging as privileged structures for chalcogen‐bonding catalysis in the focal point of conformationally immobilized σ holes on strong selenium donors in a neutral scaffold. Whereas much attention has been devoted to work out the advantages of selenium compared to the less polarizable sulfur donors, high expectations concerning bidentate, rigid, and neutral scaffolds have been generated with little experimental support. Here we report design, synthesis and evaluation of the necessary catalysts to confirm that i) bidentate BDS are more effective than their monodentate analogs, ii) conformationally immobilized scaffolds are more effective than more flexible ones, iii) cationic BDS scaffolds are more effective than neutral ones, and iv) in dicationic‐bidentate BDS, contributions from chalcogen‐bonding dominate possible contributions from ion‐pairing catalysis. These conclusions result from rate enhancements found for a Ritter ‐type anion‐binding reaction and an X‐ray crystal structure of dicationic BDS with a triflate anion bound with highest precision in the focal point of the σ holes. Abstract :